Comparison of VO2Max Capacity and Lung Vital Capacity of Junior High School Students: Highlands and Lowlands - Bafirman, Bafirman; Wahyuri, Asep Sujana; Vellya, Vellya; Zarya, Fiky; Munir, Ali (Journal of Sport Science and Education, 2023)
Highland and lowland differences affect environmental adaptation to VO2Max in athletes who train, so it is important to understand this in order to optimize training programs and achieve maximum performance. The purpose of this study was to determine the results of environmental adaptation for athletes who train in lowland highland areas to VO2Max. This type of research is quantitative research with different types of tests or comparative tests. The population in this study amounted to 1356 male students. The sample in this study was 100 students using purposive sampling techniques. The hypothesis of this study is that there is a difference in VO2Max capacity and lung vital capacity in highland students of Agam Regency with lowland students in Padang City, it can be seen from the posture of highland students having an average height of 163cm while the average lowland is 157cm, and body weight in the highlands has an average amount of 55kg while the lowlands are 51kg,  and the body mass index in the highlands averaged 21.48 while in the lowlands it was 27.38. Based on the results of data processing, it was found 1) there was a significant difference between VO2Max of junior high school students in highland areas and lowland areas p-value (2-tailed) of p=0.026 (<0.05). 2) There is a significant difference between the vital lung capacity of junior high school students in highland areas and lowland areas with p-value (2-tailed) of p=0.000 (<0.05) . It was concluded that VO2Max capacity and lung vital capacity were better in junior high school students living in the highlands than living in the lowlands in large areas with an altitude of 542 meters above undersea level.